Biology and Chemistry in works of art: a study of the state of art, perception on discent knowledge and the theme (Research, Society and Development, 2021)
The purpose of this work was to perform a bibliographical search to identify the techniques of production, analysis and materials used in the preparation of paints and pigments in paintings. This information was used for the application of a diagnostic evaluation with the objective of developing, in the future, interdisciplinary activities with the disciplines of chemistry, biology and art. The steps of this work were to carry out a research on the state of the art in the periods 2000-2020 using the Science Direct and Google Scholar platforms and a diagnostic evaluation of the use of chemistry and biology in art based on the application of a questionnaire from the Google forms for students from two educational institutions. The results obtained in Science Direct indistinctly that there is an increase of 72% in the publication of works about natural pigments and that works related to tempera painting had a decrease of 39.5%. In relation to plant pigments in works of art, there was an increase of 45.9%. Despite this, the results obtained by Google Scholar sensitive that there is an increase in searches regarding natural pigments (15%) and tempera paint (8.7%). Students aged 18-28 years and those with technical education demonstrated to develop their best answers, while those aged 51-61 years have greater difficulty in preparing their answers. It was also observed that students, in general, responded more adequately to questions that were more related to their area of ​​training.